Taxonomy of educational objectives - Akbar, Muhammad Dirja; Arbeni, Wawan; Balqis, Ummaimah; Hetiara, Rani; Ramadhan, Taufiq Ikhsan (EDUCTUM: Journal Research, 2026)
The taxonomy of educational objectives is a conceptual framework used to systematically classify learning objectives based on the cognitive, affective, and psychomotor domains. This taxonomy plays a crucial role in helping educators design learning objectives, learning strategies, and evaluate learning outcomes in a targeted and measurable manner. This article aims to examine the concept of the taxonomy of educational objectives, its historical development, and its relevance in contemporary educational practice. The research method used is a literature study by reviewing various sources in the form of books, journal articles, and relevant educational policy documents. The results of the study indicate that the taxonomy of educational objectives, particularly Bloom's Taxonomy and its revisions, remains the primary reference in learning planning because it provides clarity in the formulation of competency-based objectives and learning outcomes. Furthermore, the application of the taxonomy of educational objectives can improve the quality of the learning process by aligning objectives, materials, methods, and evaluations. Therefore, a comprehensive understanding of the taxonomy of educational objectives is essential for educators in improving the effectiveness and quality of education.